2021
DOI: 10.1186/s12889-021-11923-1
|View full text |Cite|
|
Sign up to set email alerts
|

Embracing challenging complexity: exploring handwashing behavior from a combined socioecological and intersectional perspective in Sierra Leone

Abstract: Background Handwashing with soap is a cost-effective, efficient health behavior to prevent various diseases. Despite its immense health benefits, the lowest prevalence of handwashing is found in low-income countries. Here, its practice is not only determined by individual behavior, but also heavily shaped by deprivations in the social and structural ecology. Moreover, handwashing barriers are not equally experienced as overlapping social identities (e.g., age and gender) intersect and create in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Figure 2 illustrates the factors livestock keepers interact with when it comes to accessing PPR vaccines at each socio-ecological level and the intersections across each [the framework was adapted from ( 50 )]. The intersectional lens illustrates how, even though some barriers are ubiquitous among livestock keepers (e.g., those at the Policy Level), the intersection of different social markers influences how these barriers are experienced.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 illustrates the factors livestock keepers interact with when it comes to accessing PPR vaccines at each socio-ecological level and the intersections across each [the framework was adapted from ( 50 )]. The intersectional lens illustrates how, even though some barriers are ubiquitous among livestock keepers (e.g., those at the Policy Level), the intersection of different social markers influences how these barriers are experienced.…”
Section: Resultsmentioning
confidence: 99%
“… SEM and Intersectionality frameworks for PPR vaccinations in Karamoja. The SEM was adapted from ( 37 ), and the combination of the SEM with the intersectional framework was adapted from ( 50 ). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study describes challenges encountered during a mixed-methods field experiment aiming to increase domestic handwashing, which was carried out by researchers originating from a WEIRD (Germany) and non-WEIRD society (Sierra Leone) and implemented in a non-WEIRD country (Sierra Leone). Further details about the study design can be found in [ 7 , 8 ]. This study was planned and implemented under the lead of the first author in collaboration with a local investigator, the third author.…”
Section: Introductionmentioning
confidence: 99%